2019
DOI: 10.1523/eneuro.0166-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of Tau Oligomers into Cortical Neurons Alters Action Potential Dynamics and Disrupts Synaptic Transmission and Plasticity

Abstract: Significance Statement The protein tau is highly expressed in neurons and is involved in maintaining neuronal structure. In diseases such as Alzheimer's disease (AD), tau can form oligomers, which consist of tau molecules joined together. There is growing evidence that these tau oligomers are toxic to neurons, although their precise actions are still being characterized. We have taken the approach of introducing structurally-defined tau-441 oligomers into neurons via the recording electrode (a method previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
81
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(104 citation statements)
references
References 52 publications
8
81
4
Order By: Relevance
“…Recent evidence has suggested that the accumulation of tau is mediated through the spreading of misfolded tau seeds from cell-to-cell and from initial brain regions throughout the brain in a trans-synaptic pattern as the disease progresses, thus proposing a prion-like mechanism for tau protein to propagate the disease ( 19 , 68 , 69 ). Furthermore, the association of diverse tau strains with different disorders suggests that they may be partly responsible for the diverse outcomes of tauopathies, explaining how the aggregation of the same protein can cause different diseases and diverse progression and phenotypes ( 61 , 70 72 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence has suggested that the accumulation of tau is mediated through the spreading of misfolded tau seeds from cell-to-cell and from initial brain regions throughout the brain in a trans-synaptic pattern as the disease progresses, thus proposing a prion-like mechanism for tau protein to propagate the disease ( 19 , 68 , 69 ). Furthermore, the association of diverse tau strains with different disorders suggests that they may be partly responsible for the diverse outcomes of tauopathies, explaining how the aggregation of the same protein can cause different diseases and diverse progression and phenotypes ( 61 , 70 72 ).…”
Section: Discussionmentioning
confidence: 99%
“…We generated the pProEx-HTa-Myc-6 × His-K18 plasmid carrying the C291R mutation (TGT > CGT, the same codon change previously reported by Marshall et al, 2015) by site-directed mutagenesis using a WT tau-K18 plasmid as a template (Karikari et al, 2017(Karikari et al, , 2019a. Protein expression and purification were achieved using our previously-characterized recombinant tau production protocols (Karikari et al, 2017(Karikari et al, , 2019aHill et al, 2019). The purified His-tagged tau-K18 constructs were used directly in functional experiments since the His-tag does not appear to affect aggregation (Huseby et al, 2019).…”
Section: Cloning Protein Expression and Purificationmentioning
confidence: 99%
“…Oligomers can be secreted from neurons via various mechanisms such as passive diffusion and exocytosis [11] as well as with neurotransmitters [12]. Other groups have shown that the propagated Tau oligomers lead to reduced long-term potentiation and increased short-term depression effect on cortical neurons, which has been partially blocked by the administration of oligomer-specific antibody [13,14]. Oligomers are the unstable species with neurotoxicity and inflammatory activity, which acts as a seed for further aggregation [13,15,16].…”
Section: Introductionmentioning
confidence: 99%